An investigation on the viability of tax e-services in ensuring taxpayers compliance and its impact on revenue collection. - Magarira, Tafara (Midlands State University, 2020)
This research seeks to investigate the viability of tax e-services in ensuring tax compliance and increased tax revenue collection using ZIMRA Harare branch at Kurima house as a case study. Some researchers were of the view that tax e-services plays a pivotal role in enhancing tax compliance and increase tax revenue collection. However, others argued that there is a negative association between tax e-filing and tax compliance and that revenue collection is influenced by other factors besides e-filing. Zimra failed to reach the amount set as target to be collected from different tax heads in 2015 and 2016 as a result of non-compliant taxpayers despite introduction of e-filing. Therefore this gave the researcher room to conduct an investigation on the viability of tax e-services in ensuring tax compliance and increased tax revenue. In conducting this research, the researcher used a descriptive case study that was both qualitative and quantitative. Data was collected through interviews from four interviewees and through questionnaires from thirty-two respondents. Data that was collected from the research showed that tax e-filing has a strong positive impact on tax compliance. It also showed that tax revenue collection increases as use of e-filing increases. Therefore, the researcher recommends companies to adopt use of electronic tax filing system so as to enable better tax compliance levels and revenue collect